Quality of life of lung cancer patients - Pękała, Marta; Kozaka, Joanna (Psychoonkologia, 2016)
Lung cancer is the main cause of death resulting from cancer diseases in the world. It is diagnosed in advanced stages for the majority of patients and characterized by unfavorable prognosis. Apart from the advancements in medicine, the radical treatment of this disease giving the chance to cure concerns only a small percentage of patients. In the mentioned situation it is very important to provide patients with the best quality of life when they are ill. The factors having crucial influence on the life quality of patients suffering from lung cancer have been described and the latest research on this topic has been presented in this paper. The work presents the influence of oncological therapy, somatic afflictions, mood disorders and strategies of dealing with illness on the life quality of patients suffering from lung cancer.